Growth and Neurodevelopmental Outcome in Preterm LBW Infants with Sepsis in India: A Prospective Cohort - Sunil J. Pawar; Tejopratap Oleti; Siluvery Bharathi; Shyamsunder Tipparaju; Ershad Mustafa (International Journal of Pediatrics)
Objective. Neonatal sepsis is associated with abnormal neurodevelopmental outcomes but not with poor growth at 9 to 15 months of corrected age in LBW infants. Design, Setting, and Participants. This is a prospective cohort study involving 128 eligible preterm low-birth-weight (LBW) infants admitted during the period of 2013-2014 to the Durgabai Deshmukh Hospital and Research Center. All patients were followed up in the outpatient Department of Pediatrics. They were divided into the sepsis and nonsepsis group. Results. A total of 94 infants were evaluated (40 in sepsis and 54 in nonsepsis group). At the age of 9–15 months, low-birth-weight infants with neonatal sepsis had an increased risk of neurodevelopmental disorders (67.5 versus 20.3%; RR: 3.31 (1.87–5.85)). There is no statistically significant difference in the growth outcomes. Conclusion. Neonatal infections are associated with the abnormal neurodevelopmental outcomes in LBW infants but there was no significant difference at growth outcome at 9 to 15 months of corrected age between both groups.